2022
DOI: 10.1038/s41390-022-02241-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetic ketoacidosis during COVID-19 pandemic: a meta-analysis of 124,597 children with diabetes

Abstract: Background Diabetic ketoacidosis (DKA) is a potentially life-threatening complication of type 1 diabetes mellitus (T1DM) that has increased during the COVID-19 pandemic. This study will not only shed light on such life-threatening complications but also be a step to increase the awareness of healthcare providers about such complications in the upcoming pandemic waves and increased dependence on telemedicine. Thus, we aimed to further investigate the increase of DKA in pediatrics. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…In contrast, fewer patients with established T1DM diagnosis had DKA during the pandemic phase. While the reported number of cases for these outcomes were relatively small, the data are consistent with current evidence reporting an increase in DKA and its severity at diagnosis (21,(26)(27)(28)(29)(56)(57)(58). These findings are likely related to delays in seeking care due to concerns about the increased risk in contracting the COVID-19 virus in healthcare facilities, and caregivers abiding by health systems messaging to divert care away from hospitals to prioritize resource utilization for COVID-19 activities (26).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, fewer patients with established T1DM diagnosis had DKA during the pandemic phase. While the reported number of cases for these outcomes were relatively small, the data are consistent with current evidence reporting an increase in DKA and its severity at diagnosis (21,(26)(27)(28)(29)(56)(57)(58). These findings are likely related to delays in seeking care due to concerns about the increased risk in contracting the COVID-19 virus in healthcare facilities, and caregivers abiding by health systems messaging to divert care away from hospitals to prioritize resource utilization for COVID-19 activities (26).…”
Section: Discussionsupporting
confidence: 84%
“…Elgenidy A et al 11 conducted a meta-analysis to investigate the increase of DKA in pediatrics at the time of the SARS-CoV-2 pandemic. In three databases, they looked for papers evaluating the frequency of diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Similarly, three systematic reviews and meta-analyses have shown an increase in the risk of developing DKA and severe DKA during the COVID-19 pandemic compared to the pre-pandemic era. [10][11][12] Besides, people with DM are disproportionately affected by COVID-19. For example, they are more susceptible to be admitted to an intensive care unit (ICU) than those non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition to reports of an increased incidence rate of diabetes, there have also been consistent reports of an increased risk of diabetic ketoacidosis (DKA), a preventable and life-threatening condition, at diabetes onset in children during the pandemic. 4,17,18 It is critical to know whether there was a sustained change in the incidence rates of both type 1 and type 2 diabetes in children because there are important implications for health resource planning for pediatric diabetes care, COVID-19-related and future pandemic-related public health measures, and immunization strategies. The primary objective of this systematic review and meta-analysis was to investigate whether there was a change in the incidence rate of types 1 and 2 diabetes in children and adolescents during the COVID-19 pandemic compared with before the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that the increase in sedentary behavior observed during the COVID-19 pandemic due to school closures and lockdown measures was associated with the increased prevalence of childhood obesity, a known risk factor for type 2 diabetes . In addition to reports of an increased incidence rate of diabetes, there have also been consistent reports of an increased risk of diabetic ketoacidosis (DKA), a preventable and life-threatening condition, at diabetes onset in children during the pandemic …”
Section: Introductionmentioning
confidence: 99%